Structural and functional properties of the rat P2X4 purinoreceptor extracellular vestibule during gating - Milos Boro Rokic; Milos Boro Rokic; Stanko S. Stojilkovic; Hana eZemkova (Frontiers in Cellular Neuroscience, 2014)
P2X receptors are ATP-gated cation channels consisting of three subunits that are mutually intertwined and form an upper, central, and extracellular vestibule with three lateral portals and the channel pore. Here we used cysteine and alanine scanning mutagenesis of the rat P2X4R receptor V47-V61 and K326-N338 sequences to study structural and functional properties of extracellular vestibule during gating. Cysteine mutants were used to test the accessibility of these residue side chains to cadmium during closed-open-desensitized transitions, whereas alanine mutants served as controls. This study revealed the accessibility of residues E51, T57, S59, V61, K326, and M336 to cadmium in channels undergoing a transition from a closed-to-open state and the accessibility of residues V47, G53, D331, I332, I333, T335, I337, and N338 in channels undergoing a transition from an open-to-desensitized state; residues E56 and K329 were accessible during both transitions. The effect of cadmium on channel gating was stimulatory in all reactive V47-V61 mutants and inhibitory in the majority of reactive K326-N338 mutants. The rat P2X4 receptor homology model suggests that residues affected by cadmium in the closed-to-open transition were located within the lumen of the extracellular vestibule and toward the central vestibule; however, the residues affected by cadmium in the open-to-desensitized state were located at the bottom of the vestibule near the pore. Analysis of the model assumed that there is ion access to extracellular and central vestibules through lateral ports when the channel is closed, with residues above the first transmembrane domain being predominantly responsible for ion uptake. Upon receptor activation, there is passage of ions toward the residues located on the upper region of the second transmembrane domain, followed by permeation through the gate region.